Borrow or Serve? An Economic Analysis of Options for Financing a Medical School Education. (July 2017) - Marcu, Mircea I.; Kellermann, Arthur L.; Hunter, Christine; Curtis, Jerri; Rice, Charles; Wilensky, Gail R.
Abstract : Purpose: To understand the long-term economic implications of key pathways for financing a medical school education. Method: The authors calculated the net present value (NPV) of cash flow over a 30-year career for a 2013 matriculant associated with (1) self-financing, (2) federally guaranteed loans, (3) the Public Service Loan Forgiveness program, (4) the National Health Service Corps, (5) the Armed Forces Health Professions Scholarship Program, and (6) matriculation at the Uniformed Services University of the Health Sciences. They calculated the NPV for students pursuing one of four specialties in two cities with divergent tax policies. Borrowers were assumed to have a median level of debt ($180, 000), and conservative projections of inflation, discount rates, and income growth were employed. Sensitivity analyses examined different discount and income growth rates, alternative repayment strategies, and various lengths of public-sector service by scholarship recipients. Results: For those wealthy enough to pay cash or fortunate enough to secure a no-strings scholarship, self-financing produced the highest NPV in almost every scenario. Borrowers start practice $300, 000 to $400, 000 behind their peers who secure a national service scholarship, but those who enter a highly paid specialty, such as orthopedic surgery, overtake their national service counterparts 4 to 11 years after residency. Those in lower-paid specialties take much longer. Borrowers who enter primary care never close the gap. Conclusions: Over time, the value of a medical degree offsets the high up-front cost. Debt avoidance confers substantial economic benefits, particularly for students interested in primary care. Abstract : Supplemental Digital Content is available in the text.